Atlas of the Gulf states - Cadène, Philippe. (Middle East and Islamic Studies E-Books Online, Collection 2013, ISBN: 9789004248731., 2013)
The Arab Gulf States possess more than half of the planet's crude oil reserves, and their gas reserves are immense. The transition from being rental economies to producing economies has caused rapid and significant changes, including the influx of foreign (Arab and Asian) manual laborers, and spectacular urban development, particularly along the coast. This Atlas of the Gulf States contains more than 150 maps and graphs based on recent data. It offers a survey of the history and economic and urban development of the Gulf region. For Iraq, Kuwait, Saudi Arabia, Qatar, Bahrain, the United Arab Emirates, Oman, and Iran, this atlas offers detailed maps, plans and statistics for the relevant provinces as well as the most important cities. This Atlas is an updated translation from the French edition (2011), with a more extensive bibliography and an index.